2021
DOI: 10.1177/1045389x211048223
|View full text |Cite
|
Sign up to set email alerts
|

Design and multi-objective optimization of magnetorheological damper considering vehicle riding comfort and operation stability

Abstract: Mostly, magnetorheological (MR) dampers were optimized based on individual performance, without considering the influence of structure parameters change on vehicle performance. Therefore, a multi-objective optimization scheme of MR damper based on vehicle dynamics model was proposed. The finite element method was used to analyze magnetic flux density distribution in tapered damping channel under different structure parameters. Furthermore, the damping force expression of the tapered flow mode MR damper was der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Orthogonal experimental design, an experimental design method to study multiple factors and levels. Orthogonal optimization is used to study the importance of the influence of each factor on the damping performance in different situations (Deng et al, 2022a). The purpose of this orthogonal test is to find the optimal structure size of the stepped bypass magnetorheological damper.…”
Section: Parameter Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthogonal experimental design, an experimental design method to study multiple factors and levels. Orthogonal optimization is used to study the importance of the influence of each factor on the damping performance in different situations (Deng et al, 2022a). The purpose of this orthogonal test is to find the optimal structure size of the stepped bypass magnetorheological damper.…”
Section: Parameter Optimizationmentioning
confidence: 99%
“…The proposed damper has a specific pole shape function, and the damping coefficient is changed by changing the effective area of the main hole, and the mathematical modeling of the pole shape function is carried out, and the feasibility of the new magnetorheological damper is verified by example. At present, many people have carried out a lot of optimization work on the structure of the magnetorheological damper, in order to improve the structure and related performance of the damper (Deng et al, 2022a; Hu et al, 2021; Huina et al, 2021; Nanthakumar and Jancirani, 2019). In order to improve the damper-related performance of the magnetorheological damper in a limited structure, some scholars have studied the application of metal foam in the magnetorheological damper (Yao and Pecht, 2020; Yao and Peng, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The total pressure drop of the tapered flow channel is 21 Therefore, the output damping force of the MR damper can be calculated by the following formula Where, normalΔ p η is the viscous pressure drop of the tapered channel, normalΔ p τ is the yield pressure drop of the tapered channel, normalΔ p is the total pressure drop of the tapered channel, μ is the fluid viscosity without an applied magnetic field, R 1 and R 2 are the inner and outer core radius, q is flow rate in damping channel, H 0 is the gap width of the damping channel, θ is the tapered angle of the damping channel, L 1 is the effective magnetic pole length, and L 1 = L 2, τ y is the shear yield stress, 22 C 1 and C 2 are the modified coefficient, F η is the viscous damping force, F τ is the controllable damping force, …”
Section: Vehicle Semi-active Suspension Designmentioning
confidence: 99%
“…To solve the problem of uncertainty of external factors, an adaptive fuzzy sliding mode control measurement that combines adaptive fuzzy control with sliding mode control was proposed, and research has shown that this control strategy has a good response to complex signal inputs (Shin et al, 2016). In addition, to reduce the influence of external factors on the performance of semi-active suspensions, researchers have proposed various solutions based on modern robust control strategies (Deng et al, 2022; Lee et al, 2011; Ning et al, 2018; Xu and Lam, 2001). However, these studies can only weaken the influence of individual external factors on the vehicle state.…”
Section: Introductionmentioning
confidence: 99%